Altitude-dependent agro-ecologies impact the microbiome diversity of scavenging indigenous chicken in Ethiopia - Glendinning, L.; Jia, X.; Kebede, Adebabay; Oyola, Samuel O.; Park, J.-E.; Park, W.; Assiri, A.; Holm, J.B.; Kristiansen, K.; Han Jianlin; Hanotte, Olivier H. (BioMed Central, 2024)
Background: Scavenging indigenous village chickens play a vital role in sub-Saharan Africa, sustaining the livelihood of millions of farmers. These chickens are exposed to vastly different environments and feeds compared to commercial chickens. In this study, we analysed the caecal microbiota of 243 Ethiopian village chickens living in different altitude-dependent agro-ecologies.